2020
DOI: 10.1111/febs.15263
|View full text |Cite
|
Sign up to set email alerts
|

SUMO system – a key regulator in sarcomere organization

Abstract: Skeletal muscles constitute roughly 40% of human body mass. Muscles are specialized tissues that generate force to drive movements through ATP-driven cyclic interactions between the protein filaments, namely actin and myosin filaments. The filaments are organized in an intricate structure called the 'sarcomere', which is a fundamental contractile unit of striated skeletal and cardiac muscle, hosting a fine assembly of macromolecular protein complexes. The micrometer-sized sarcomere units are arranged in a reit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Muscle fiber types are heterogeneous, displaying protein isoform-specific signatures that impart distinctive functionalities to meet diverse physiological demands ( Armstrong & Phelps, 1984 ; Bottinelli & Reggiani, 2000 ; Bottinelli, 2001 ; Schiaffino & Reggiani, 2011 ; Schiaffino et al, 2020 ). Composite muscle fiber profiles are a result of coordinated regulation of gene expression ( Firulli & Olson, 1997 ; Black & Olson, 1998 ; Majesky, 2007 ), co-integrated with protein isoform transitions facilitated by alternative splicing ( Smith et al, 1989 ; Guo et al, 2010 ; Kalsotra & Cooper, 2011 ; Nikonova et al, 2020 ), accompanied by post-translational modifications ( Anthony et al, 2002 ; Michele & Campbell, 2003 ; Wells et al, 2003 ; Nayak & Amrute-Nayak, 2020 ). The underlying molecular changes are initially regulated by the intrinsic developmental program ( Firulli & Olson, 1997 ; Kablar & Rudnicki, 2000 ), and later modulated by nerve stimulation, physiological demands, and pathophysiological conditions ( Hughes et al, 1993 ; Pette & Staron, 2001 ; Schiaffino et al, 2007 ; Pistoni et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle fiber types are heterogeneous, displaying protein isoform-specific signatures that impart distinctive functionalities to meet diverse physiological demands ( Armstrong & Phelps, 1984 ; Bottinelli & Reggiani, 2000 ; Bottinelli, 2001 ; Schiaffino & Reggiani, 2011 ; Schiaffino et al, 2020 ). Composite muscle fiber profiles are a result of coordinated regulation of gene expression ( Firulli & Olson, 1997 ; Black & Olson, 1998 ; Majesky, 2007 ), co-integrated with protein isoform transitions facilitated by alternative splicing ( Smith et al, 1989 ; Guo et al, 2010 ; Kalsotra & Cooper, 2011 ; Nikonova et al, 2020 ), accompanied by post-translational modifications ( Anthony et al, 2002 ; Michele & Campbell, 2003 ; Wells et al, 2003 ; Nayak & Amrute-Nayak, 2020 ). The underlying molecular changes are initially regulated by the intrinsic developmental program ( Firulli & Olson, 1997 ; Kablar & Rudnicki, 2000 ), and later modulated by nerve stimulation, physiological demands, and pathophysiological conditions ( Hughes et al, 1993 ; Pette & Staron, 2001 ; Schiaffino et al, 2007 ; Pistoni et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Muscles develop to accommodate a heterogeneous composition of fiber-types with protein isoformspecific signatures that impart distinctive functionalities to meet diverse physiological demands (Armstrong and Phelps, 1984;Bottinelli, 2001;Bottinelli and Reggiani, 2000;Schiaffino and Reggiani, 2011;Schiaffino et al, 2020). Composite muscle fiber profiles are a result of coordinated regulation of gene expression (Black and Olson, 1998;Firulli and Olson, 1997;Majesky, 2007), co-integrated with protein isoform transitions facilitated by alternative splicing (Guo et al, 2010;Kalsotra and Cooper, 2011;Nikonova et al, 2020;Smith et al, 1989), accompanied by post-translational modifications (Anthony et al, 2002;Michele and Campbell, 2003;Nayak and Amrute-Nayak, 2020;Wells et al, 2003). The underlying molecular changes are initially regulated by the intrinsic developmental program (Firulli and Olson, 1997;Kablar and Rudnicki, 2000), and later modulated by nerve stimulation, physiological demands and patho-physiological conditions (Hughes et al, 1993;Pette and Staron, 2001;Pistoni et al, 2010;Schiaffino et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These filaments are organized in a structure called sarcomere. SUMOylation has, in recent years, emerged as a key regulator in sarcomere organization [31]. It was shown that the level of mitochondrial-specific IMM lipid CL oscillates during the diurnal cycle in myotubes [32].…”
Section: Physiologic Situationmentioning
confidence: 99%